Plasmonics: Hollow Plasmonic U‐Cavities with High‐Aspect‐Ratio Nanofins Sustaining Strong Optical Vortices for Light Trapping and Sensing 6/2014). Issue 6 (June 2014) - Ho, Ya‐Lun; Portela, Alejandro; Lee, Yaerim; Maeda, Etsuo; Tabata, Hitoshi; Delaunay, Jean‐Jacques
<x xml:space="preserve">Abstract</x> Perfect light confinement in hollow, high‐aspect‐ratio, plasmonic U‐shaped cavities is demonstrated by J.‐J. Delaunay and co‐workers on page 522 through the coupling of the cavity ridge hot spots with scalable mirrored surface plasmon U‐cavity resonances. Light is fully trapped in intense optical vortices and confined on the extended cavity surfaces, thus accumulating energy in tunable, strong, and sharp resonances that generate sensitive reflectance dips. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>